Sosialisasi Strategi Jitu Memilih Program Studi Dan Peluang Beasiswa Bagi Siswa Kelas XII MAN 1 Padang Pariaman Dan SMKN 1 Enam Lingkung - Yofina Mulyati; Yusnaena; Idwar; Alvin Alfian; Yentisna; Yulisran Buana Putra; Davina; Azzura (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Education is an important aspect in the current era of modernization. Choosing the right study program in college is a crucial step for class XII students to prepare for their future. In this context, socialization regarding strategies for choosing study programs and scholarship opportunities is very relevant. With the right information, it is hoped that students can make intelligent decisions and get the opportunity to continue their education to a higher level. Community service activities are carried out through lecture, discussion and question and answer methods. The service team from Dharma Andalas University provided material using Power Point to make it easier for participants to understand. In addition, discussion and question and answer sessions were held to ensure deeper understanding. Multi-media tools such as laptops and LCD projectors are used to ensure the effectiveness and interest of participants in socialization activities. With this interactive method, it is hoped that participants can gain a good understanding of strategies for choosing study programs and scholarship opportunities.